Effect of cumulative radiation exposure from Coronary catheterization on lung cancer mortality - Jin Liu; Shiqun Chen; Yang Zhou; Xueyan Zheng; Ruilin Meng; Ning Tan; Yong Liu (BMC Cancer, 2023)
Abstract Background Coronary catheterization (CC) procedure inevitably exposes patients with cardiovascular disease (CVD) to radiation, while cumulative radiation exposure may lead to higher risk of cancer. Methods This multi-center, retrospective study was based on the CC procedure in Cardiorenal ImprovemeNt II cohort (CIN-II, NCT05050877) among five regional central tertiary teaching hospitals in China between 2007 and 2020. Patients without known cancer were stratified according to the times they received CC procedure. Baseline information from their last CC procedure was analyzed. Cox regression and Fine-Gray competing risk models were used to assess the relationship between cumulative radiation exposure from CC procedures and cancer-specific, all-cause and cardiovascular mortality. Results Of 136,495 hospitalized survivors without cancer at baseline (mean age: 62.3 ± 11.1 years, 30.9% female), 116,992 patients (85.7%) underwent CC procedure once, 15,184 patients (11.1%) on twice, and 4,319 patients (3.2%) underwent CC procedure more than three times. During the median follow-up of 4.7 years (IQR: 2.5 to 7.4), totally 18,656 patients (13.7%) died after discharge, of which 617 (0.5%) died of lung cancer. Compared with the patients who underwent CC procedure once, the risk of lung cancer mortality increased significantly with the increase of the number of CC procedure (CC 2 times vs. 1 time: HR 1.42, 95% CI 1.13 to 1.78, P < 0.001; CC ≥ 3 times vs. 1 time: HR 1.64, 95%CI 1.13 to 2.39, P < 0.05). Similar results were observed in all-cause mortality and cardiovascular mortality, but not in other cancer-specific mortality. Conclusions Our data suggest that substantial proportion of CVD patients are exposed to multiple high levels of low-dose ionizing radiation from CC procedure, which is associated with an increased risk of cancer mortality in this population. Trial registration ClinicalTrials.gov: NCT05050877; URL: http://www.clinicaltrials.gov ; 21/09/2021.